2008
DOI: 10.1002/macp.200800180
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Polymer Light‐Emitting Diodes Derived from a Platinum(II) Polyyne Containing the Bithiazole Ring

Abstract: The synthesis, thermal, and photoluminescence properties of novel platinum metallopolyynes of bithiazole derivatives trans‐[Pt(PR3)2‐C≡C‐Ar‐C≡C]n (Ar = 4,4′‐dibutyl‐2,2′‐bithiazole‐5,5′‐diyl P1; 4,4′‐dinonyl‐2,2′‐bithiazole‐5,5′‐diyl P2) and their molecular model complexes are described. The structural properties of the dinuclear model compound for P1 have been examined by X‐ray crystallography. In view of the electron‐donating and electron‐withdrawing nature of the thiazole rings in the main chain, a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 86 publications
1
30
0
Order By: Relevance
“…Clearly, these nice EL performances associated the orange phosphorescent copolymers have indicated the great potential these novel phosphorescent polymers with platinum(II) polymetallayne backbones, which has been rarely explored in the field of PHOLEDs. Several years ago, we employed bithiozole-based based platinum(II) polymetallaynes as green emitters for fluorescent OLEDs, which just achieved h L of 0.11 cd A À1 [6]. At present, the yellow/orange phosphorescent polymers are in limited number compared with the ones emitting primary colors.…”
Section: Electroluminescent Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, these nice EL performances associated the orange phosphorescent copolymers have indicated the great potential these novel phosphorescent polymers with platinum(II) polymetallayne backbones, which has been rarely explored in the field of PHOLEDs. Several years ago, we employed bithiozole-based based platinum(II) polymetallaynes as green emitters for fluorescent OLEDs, which just achieved h L of 0.11 cd A À1 [6]. At present, the yellow/orange phosphorescent polymers are in limited number compared with the ones emitting primary colors.…”
Section: Electroluminescent Characterizationmentioning
confidence: 99%
“…Furthermore, some platinum(II) polymetallaynes can exhibit strong fluorescent emission at room temperature. Hence, some organic light-emitting diodes (OLEDs) have been fabricated with platinum(II) polyynes containing bithiazole unit [6]. All these important applications associated with polymetallaynes has been afforded by their diverse photophysical behaviors which can be effectively manipulated through tuning the structure of organic spacers [2b], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Wong and Djurišić's team, on the other hand, prepared organometallic PAEs containing platinum atoms and bithiazole units (cf., Scheme 5) with optical band gaps down to 2.40 eV and demonstrated their applications as emitting layers in the fabrication of polymer lightemitting diodes. [20] We hope that this Series will serve as a stimulus for new research efforts to realize the full potentials of acetylenic monomers as a group of versatile building blocks for the construction of …”
Section: This Special Article Seriesmentioning
confidence: 99%
“…Despite many examples of platinum(II)–polyyne polymers and carbazole‐based polymers, their thermal analysis studies have usually reported only the initiation temperatures of thermal decomposition . In other words, there have been, to the best of our knowledge, no detailed reports on the thermal degradation mechanism.…”
Section: Introductionmentioning
confidence: 99%